Geopolitical Shifts in the International Order Post-COVID-19: Towards a Multipolar World or Strategic Chaos? - Salah Aldeen Mohammed Altaef (Journal of Libyan Academy Bani Walid, 2025)
With a focus on the factors influencing the future of global power relations, this study explores the geopolitical changes in the international system in the wake of COVID-19. In addition to highlighting the rapid development of China as a major economic and technological power, the study also reveals how the pandemic served as a strategic turning point, demonstrating a relative reduction in U.S. hegemony due to internal political and economic issues. Despite ongoing internal strife, Europe has pushed for more strategic autonomy, while Russia has maintained its influence in Eurasia and Africa through its forceful actions. The results show that in addition to undermining economies, the pandemic revealed the weaknesses of global organisations like the World Health Organisation and the United Nations, which found it difficult to adequately handle non-traditional challenges. Furthermore, the crisis has increased non-traditional security threats like cybersecurity, climate change, and global health issues, which has strengthened a state of strategic disorder in the global system. According to the report, the Arab world and Africa have a limited ability to influence global restructuring because of structural flaws in their political and economic capacities. In light of this, the study emphasises the critical need to fortify multilateral institutions to facilitate more effective collective responses, empower fragile regions politically and economically so they can more actively contribute to global stability, and strengthen international cooperation to address common global challenges.